Upaya Meningkatkan Motivasi dan Hasil Belajar Biologi pada Konsep Keanekaragaman Hayati dengan Metode Discovery Learning (Penelitian Tindakan di Kelas X IPA 1 SMAN 3 Metro) - Rosita, Hepi (STKIP PGRI Bandar Lampung, 2020)
In learning of Biology, motivation is needed by students to build self-readiness in improving and storing learning information delivered by educators at school. Therefore, this study aims to determine the increase in motivation and learning outcomes of class X IPA 1 SMA Negeri 3 Metro on biodiversity material using the discovery method. The research design used was classroom action research. Data collection procedures in the study include observation, documentation, and interviews. Data collection techniques and tools are test and non-test. The results showed that the average student learning motivation before the action was taken was 40.27 in the sufficient category, while the average learning outcome was at a score of 59. From Cycle I, the motivation aspect obtained a score of 77.83 in the good category. While the learning outcomes reached a score of 76. Furthermore, in Cycle II, the motivation aspect reached a score of 105.70 (very good), and learning outcomes obtained an average of 90. The conclusion of this study shows that there is an increase in motivation from the first cycle of 37.56% and learning outcomes 17%, Cycle II motivation increased to 27.87 and learning outcomes increased 14%.